PERENCANAAN PEMBANGKIT LISTRIK TENAGA SURYA SEBAGAI CATU DAYA PADA SISTEM POMPA AIR DI SUMUR BOR ABIANSEKA II - Ananta Mahanata, I Gusti Putu; Dwi Giriantari, Ida Ayu; Setiawan, I Nyoman (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i02.p13, 2024)
To accelerate the increase in the use of New Renewable Energy (EBT) in Bali Province in accordance with the General Regional Energy Plan (RUED), the Bali Provincial Government issued Bali Governor Circular Letter (SE) Number 5 of 2022. One of the applications of this letter is investment planning and analysis installation of a Solar Power Plant (PLTS) at the Abianseka II drilled well in Batuan Kaler Village, Gianyar. The Abianseka II drilled well is equipped with 4 pumps which on average consume 25,093.33 kWh of electricity per month. Based on the survey, the land available at the Abianseka II drilled well is sufficient for the installation of Ground Mounted PLTS covering an area of 478.5 m2. Therefore, it was decided to use 83 Jinko Solar JKM610N-78HL4-V 610 Wp modules with a total capacity of 50.6 kWp, as well as 1 LivoLtek 60 kW inverter and PLTS are capable of producing annual energy of 82,783 MWh, and have a performance ratio of 82.3%.